Study of knowledge and practices of hand washing among mothers having children under 5 years of age in urban field practicing area of Kakatiya Medical College, Warangal, Telangana, India - Begum, Rafath Unnisa; Bhavani, K. (International Journal Of Community Medicine And Public Health, 2017)
Background: Hand washing is viewed as most cost effective intervention for reducing global infections like diarrhoea, acute respiratory tract infections. According to WHO estimates, 3.8 million children aged less than five die each year from diarrhoea and ARI. WHO defines hand washing as washing hands with soap and water (HWWS) thoroughly following the five critical moments i.e. after defecation, after cleaning child’s bottom who had defecated, before cooking, eating and feeding child. Objectives of the study was to study the socio demographic profile of mothers, to study the hand washing practices among mothers having children under 5 years of age and factors influencing them and to impart knowledge about the importance of hand washing Methods: A community based descriptive cross sectional study was undertaken on mothers randomly selected in rangampet, urban field practising area of KMC, Warangal. A total of 150 mothers were interviewed using a pre-designed semi-structured questionnaire. The data was analyzed using SPSS version 22.00. Results: Mothers who washed their hands with soap and water after defecation (79.3%) and after cleaning child’s bottom (82.7%) before cooking (44.7%), before eating (44.7%) and before feeding the child (41.3%). The women who didn’t wash their hands properly (used only water) after defecation (20.7%) and after cleaning a child who has just defecated (17.3%) cited the absence of soap or water at the designated site of hand washing as the reason for not doing so. 78.7% have told that hand washing is important in prevention of diseases. 16.7% have given the response that they don’t know the importance of hand washing. Conclusions: The study shows hand washing after critical moments is critically low. It can be suggested that interventions by educating target an increase in hand washing practices. Innovative social marketing approaches may help in adoption of proper hand washing behaviour.